2023
DOI: 10.3390/molecules28031231
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Ruthenium(II) and Iridium(III) Based Complexes for Anion Sensing

Abstract: Improvements in the design of receptors for the detection and quantification of anions are desirable and ongoing in the field of anion chemistry, and remarkable progress has been made in this direction. In this regard, the development of luminescent chemosensors for sensing anions is an imperative and demanding sub-area in supramolecular chemistry. This decade, in particular, witnessed advancements in chemosensors based on ruthenium and iridium complexes for anion sensing by virtue of their modular synthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 155 publications
0
6
0
Order By: Relevance
“…1 The maximum of the first intense absorption band. 2 The maximum of the low-energy band. * Measured at λ abs 2 .…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The maximum of the first intense absorption band. 2 The maximum of the low-energy band. * Measured at λ abs 2 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Ruthenium (II) polypyridine complexes have a wide range of applications: they are used as photocatalysts [ 1 ], luminescent chemosensors [ 2 ], dyes in Grätzel cells [ 3 , 4 , 5 ], anticancer drugs [ 6 ], etc. The main feature of these complexes is the presence of intense absorption in the visible region, which makes them very promising for usage in light conversion molecular devices.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Among existing fluorescent probes, transition metal complexes have the advantages of long phosphorescence lifetimes, unique binding modes and large Stokes shifts compared with organic fluorophores. 11,12 In a previous study, Yu et al revealed by time-course imaging that a ruthenium (Ru) complex enabled real-time imaging of Aβ growth without disturbance. 13 Therefore, we aimed to design and synthesize a Ru complex that binds specifically to Aβ oligomers to monitor their growth.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, luminescent probes have attracted attention due to their simplicity and high selectivity. [26][27][28][29] Herein, a triazole coupled organosilane based double responsive probe (absorbance and emission) has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mentioned techniques suffer several drawbacks like complex sample handling, high‐cost equipment, toxic chemicals and are laborious. Recently, luminescent probes have attracted attention due to their simplicity and high selectivity [26–29] . Herein, a triazole coupled organosilane based double responsive probe (absorbance and emission) has been developed.…”
Section: Introductionmentioning
confidence: 99%